Efektifitas Waktu dan Dosis Pemberian NPK terhadap Produksi Jagung Manis (Zea mays saccharata Sturt) pada Dataran Tinggi - Irma Lisa Sridanti; Hot Himanson Saragih (Seminar Nasional Lahan Suboptimal, 2018)
Sridanti et al, 2019. Effectiveness of Time and Dosage for Giving NPK to the Production of Sweet Corn (Zea mays saccharata Sturt) in the Highlands. pp. 28-31. Sweet corn plants will not provide maximum results if the nutrients needed are not enough. Fertilization can increase yields quantitatively and qualitatively. The purpose of this study was to determine the effect of fertilizing time and the ideal dose for sweet corn. This research was carried out in Mojorejo Village, Selupu Rejang District, Rejang Lebong Regency at an altitude of + 0.050 meters above sea level (m asl). This study uses Factorial Randomized Block Design (RAKF). Observations and measurements were carried out on the main variables in the form of fruit weight, ear length and ear diameter without cornhusk (generative parts) as well as supporting variables such as plant height and number of leaves (vegetative parts). All data are analyzed by variance, and if F table is greater than F, the count is tested further using DMRT. The results showed 50 grams of NPK fertilizer significantly different from the average plant height and not significantly different from fertilization time.